THE DEFENSE ECONOMIC STRATEGY THROUGH DIPLOMACY AIMS TO INCREASE DEFENSE ENTREPRENEURSHIP FOR A GLOBALLY COMPETITIVE GOLDEN INDONESIA IN 2045 - Samingan, Muhamad (Jurnal Pertahanan dan Bela Negara, 2024)
In an era of increasingly complex geopolitical dynamics and intense global competition, a country’s national defense becomes the main foundation to ensure security and sustainable development. Defense Entrepreneurship emerges as a new paradigm that combines entrepreneurial principles with the strategic needs of national defense, a national vision to make Indonesia a developed nation by 2045. Smart economic diplomacy involves a synergistic interaction between defense innovation, strategic investment and international cooperation, creating the foundation of a resilient and competitive national defense on the global stage. With the Multy-Track Diplomacy approach being the main foundation in realizing Defense Entrepreneurship Indonesia Emas 2045. The purpose of this research is to analyze Indonesia in building strong partnerships with other countries, increasing defense capacity together, and expanding access to global markets. Qualitative research methods and data collection techniques in the form of Literature Studies and Library Research. The results of this study indicate that entrepreneurship strengthens national defense but also makes a positive contribution to Indonesia’s economic growth and economic diplomacy.